Case reports: three novel variants in PCCA and PCCB genes in Chinese patients with propionic acidemia - Qi Yang; Hong Xu; Jingsi Luo; Mengting Li; Sheng Yi; Qinle Zhang; Guoxing Geng; Shihan Feng; Xin Fan (BMC, 2020)
Abstract Background Propionic acidemia (PA) is an autosomal recessive metabolic disorder caused by the deficiency of the mitochondrial protein propionyl-CoA carboxylase (PCC) and is associated with pathogenic variants in either of the two genes PCCA or PCCB. The present study aimed to identify the genetic cause of three Chinese patients with PA. Case presentation Three Chinese PA patients were diagnosed by using gas chromatography-mass spectrometry(GC-MS), tandem mass spectrometry (MS/MS) and molecular diagnostic methods. All patients had onset in the neonatal period. One patient died of infection and metabolic decompensation, and the other two had mild to moderate developmental delay/mental retardation. Mutation analysis of the PCCA gene identified that patient 1 carried the compound heterozygous c.1288C > T(p.R430X) and c.2002G > A(p.G668R), and patient 2 was homozygous for the c.1426C > T(p.R476X) mutation. Mutation analysis of the PCCB gene identified that patient 3 harbored the compound heterozygous mutations c.359_360del AT(p.Y120Cfs*40) and c.1398 + 1G > A. Among these mutations, three (c.1288C > T, c.359_360del AT and c.1398 + 1G > A) are novel. Conclusions We reported three Chinese PA patients who had PCCA or PCCB mutants. Among them, in the PCCA gene, c.1288C > T(p.R430X) was a nonsense mutation, resulting in a truncated protein. c.359_360del AT was a frameshift mutation, leading to a p.Y120Cfs*40 change in the amino acid sequence in the PCCB protein. c.1398 + 1G > A was a splicing mutation, causing skipping of the exons 13-14. In conclusion, the novel mutations uncovered in this study will expands the mutation spectrum of PA.